2014
DOI: 10.11005/jbm.2014.21.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Association of Arterial Stiffness and Osteoporosis in Healthy Men Undergoing Screening Medical Examination

Abstract: BackgroundAssociation of arterial stiffness and osteoporosis has been previously reported in women. However, this association is still controversial for men. Therefore, we investigated correlation of arterial stiffness and osteoporosis by measuring brachial-ankle (ba) pulse wave velocity (PWV) and bone mineral density (BMD).MethodsWe reviewed medical charts of 239 people (women: 128, men: 111) who visited the Health Promotion Center, retrospectively. ba-PWV was measured by automatic wave analyzer. Lumbar spine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Recently, some reports found that BMD is not associated with baPWV in men . However, these studies were conducted in the general population.…”
Section: Study Strengths and Limitationsmentioning
confidence: 96%
See 2 more Smart Citations
“…Recently, some reports found that BMD is not associated with baPWV in men . However, these studies were conducted in the general population.…”
Section: Study Strengths and Limitationsmentioning
confidence: 96%
“…The findings on the relationship between BMD and baPWV are inconsistent. Some reports demonstrate that BMD is associated with baPWV in patients with OP, whereas other studies reveal that the association is not significantly different . The discrepancies in these results may be attributed to small sample sizes, different sexes, and select populations.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…A significant inverse correlation between PWV and BMD was found in the general population in Macedonia [37]. A few studies performed in Japan and Korea have reported similar results in women [11, 34, 35]. However, other studies conducted in Japan and Korea have found no association between lumbar spine BMD and PWV in women [10, 22].…”
Section: Discussionmentioning
confidence: 99%
“…The association between BMD and baPWV has mainly been evaluated in women, and the conclusions drawn from studies are inconsistent and controversial [11, 34-37]. A significant inverse correlation between PWV and BMD was found in the general population in Macedonia [37].…”
Section: Discussionmentioning
confidence: 99%